Fat-Specific Sirt6 Ablation Sensitizes Mice to High-Fat Diet–Induced Obesity and Insulin Resistance by Inhibiting Lipolysis - Kuang, Jiangying; Zhang, Yuwei; Liu, Qinhui; Shen, Jing; Pu, Shiyun; Cheng, Shihai; Chen, Lei; Li, Hong; Wu, Tong; Li, Rui; Li, Yanping; Zou, Min; et al. (Diabetes (New York, N.Y.), 2017)
Sirt6 is an NAD+-dependent deacetylase that is involved in the control of energy metabolism. However, the tissue-specific function of Sirt6 in the adipose tissue remains unknown. In this study, we showed that fat-specific Sirt6 knockout (FKO) sensitized mice to high-fat diet–induced obesity, which was attributed to adipocyte hypertrophy rather than adipocyte hyperplasia. The adipocyte hypertrophy in FKO mice likely resulted from compromised lipolytic activity as an outcome of decreased expression of adipose triglyceride lipase (ATGL), a key lipolytic enzyme. The suppression of ATGL in FKO mice was accounted for by the increased phosphorylation and acetylation of FoxO1, which compromises the transcriptional activity of this positive regulator of ATGL. Fat-specific Sirt6 KO also increased inflammation in the adipose tissue, which may have contributed to insulin resistance in high-fat diet–fed FKO mice. We also observed that in obese patients, the expression of Sirt6 expression is reduced, which is associated with a reduction of ATGL expression. Our results suggest Sirt6 as an attractive therapeutic target for treating obesity and obesity-related metabolic disorders.